2015
DOI: 10.1158/1078-0432.ccr-14-1705
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Response and Circulating Tumor Cell Count Identifies Treated HER2+ Inflammatory Breast Cancer Patients with Excellent Prognosis: BEVERLY-2 Survival Data

Abstract: Purpose: The BEVERLY-2 single-arm phase II trial assessed the efficacy and safety of combining neoadjuvant chemotherapy with bevacizumab and trastuzumab for the treatment of HER2-positive inflammatory breast cancer (IBC). Here, we report the results of a preplanned survival analysis at 3 years of follow-up, along with the association between outcome and circulating biomarkers and pathologic complete response (pCR).Experimental Design: Patients received fluorouracil, epirubicin, cyclophosphamide, and bevacizuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 40 publications
1
28
0
2
Order By: Relevance
“…Finally, 50 studies were eligible for meta-analysis (Fig. 1)4591112131415161718192021222324252627282930313233343536373839404142434445464748495051525354555657.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 50 studies were eligible for meta-analysis (Fig. 1)4591112131415161718192021222324252627282930313233343536373839404142434445464748495051525354555657.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, clinical trial design should also take into account the positive correlation between pathologic complete response rate (pCR) with disease-free survival benefit for a subset of patients with IBC (i.e. : HER2+ IBC) as trials assessing the efficacy of neoadjuvant treatments are inherently shorter [29]. This manuscript aims to review the discoveries in the biology of IBC while highlighting the rationale for developmental therapeutics approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, although we failed to find a significant association between DFS and CTC dynamic changes, all eight patients achieved both pCR and CTC‐negative conversion after NCT and were recurrence‐free within the follow‐up period. The BEVERLY‐2 trial was a prospective study that included 52 inflammatory BC patients, which is a very aggressive subtype of BC, and found that CTC‐positivity (>1 CTC/7.5 mL) dropped from 35% to 7% with NCT. Patients with at least one positive CTC had a DFS of 54%, compared with a DFS of 83% in patients where no CTCs were detected during neoadjuvant stages ( P = .018).…”
Section: Discussionmentioning
confidence: 99%